Legal issues posed by the internet - The Malaysian perspective - Khaw, L.T. (1995)
Access to the Internet in Malaysia is gaining popularity and becoming more widespread. Although specific legal issues relating to the Internet have yet to be brought before the courts, Malaysia is in the process of examining the legal issues posed by the Internet and information technology, and legislative action and changes may be proposed. In this paper, I will provide the Malaysian perspective to the issues raised by Dr Gordon Hughes in his paper.